The essential Hirschman - Hirschman, Albert O. (Princeton University Press, 2013)
The Essential Hirschman brings together some of the finest essays in the social sciences, written by one of the twentieth century's most influential and provocative thinkers. Albert O. Hirschman was a master essayist, one who possessed the rare ability to blend the precision of economics with the elegance of literary imagination. In an age in which our academic disciplines require ever-greater specialization and narrowness, it is rare to encounter an intellectual who can transform how we think about inequality by writing about traffic, or who can slip in a quote from Flaubert to reveal something surprising about taxes. The essays gathered here span an astonishing range of topics and perspectives, including industrialization in Latin America, imagining reform as more than repair, the relationship between imagination and leadership, routine thinking and the marketplace, and the ways our arguments affect democratic life. Throughout, we find humor, unforgettable metaphors, brilliant analysis, and elegance of style that give Hirschman such a singular voice.Featuring an introduction by Jeremy Adelman that places each of these essays in context as well as an insightful afterword by Emma Rothschild and Amartya Sen, The Essential Hirschman is the ideal introduction to Hirschman for a new generation of readers and a must-have collection for anyone seeking his most important writings in one book"--